The Art of Being In-between : Native Intermediaries, Indian Identity, and Local Rule in Colonial Oaxaca - Yannakakis, Yanna, 1967- (Book collections on Project MUSE., 2008)
Asks how elite native intermediaries conversant in Spanish language, legal rhetoric, and personal demeanor shaped the political and cultural landscape of colonialism.